Luteolin Prevents Cardiac Dysfunction and Improves the Chemotherapeutic Efficacy of Doxorubicin in Breast Cancer - Shi, Youyang; Li, Feifei; Shen, Man; Sun, Chenpin; Hao, Wei; Wu, Chunyu; Xie, Ying; Zhang, Shuai; Gao, Hongzhi; Yang, Jianfeng; Zhou, Zhongyan; Gao, Dongwen; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Doxorubicin (Dox) is one of the most effective chemotherapy agents used in the treatment of solid tumors and hematological. However, it causes dose-related cardiotoxicity that may lead to heart failure in patients. Luteolin (Lut) is a common flavonoid that exists in many types of plants including fruits, vegetables, and medicinal herbs which has been studied using for treating various diseases such as hypertension, inflammatory disorders, and cancer. In this study, we evaluated the cardioprotective and anticancer effects of Lut on Dox-induced cardiomyopathy in vitro and in vivo to explore related mechanisms focusing on alleviating Drp1-mediated mitochondrial apoptosis. Methods: MTT and LDH assay were used to determine the viability and of toxicity cardiomyocytes treated with Dox and Lut. The level of ROS was examined by flow cytometry and the mitochondrial morphology was assessed on electron and confocal microscopy. The level of apoptosis was examined by Hoechst 33258. The protein levels of myocardial fission protein and apoptosis related protein were examined using western blotting. A transcriptome analysis of the protective effect of Lut against Dox-induced Cardiac toxicity in myocardial cells was performed using RNA-seq technology. The protective effects of Lut against cardiotoxicity mediated by Dox in zebrafish were quantified. Experiments were then further employed and revealed that Lut increase the antitumor activity of Dox in breast cancer both in vitro and in vivo. Results: Lut ameliorated Dox-induced toxicity in both H9c2 and AC16 cells. The level of oxidative stress was down regulated by Lut after Dox treatment of myocardial cells. Lut effectively blunted the increased mitochondria fission post Dox stimulation in cardiomyocyte. Apoptosis, Fission protein Drp1 and its ser 616 phosphorylation were also increased post Dox and reduced by Lut. In zebrafish model, Lut significantly preserved the ventricular function of zebrafish after Dox treatment. Moreover, in mouse model, Lut enhanced Dox-induced cytotoxicity in triple negative breast cancer by inhibiting proliferation, metastasis and inducing apoptosis.